Tumor necrosis factor-alpha triggers a cytokine cascade yielding postoperative cognitive decline. - Terrando, N; Monaco, C; Ma, D; Foxwell, B; Feldmann, M; Maze, M (2010)
Cognitive decline following surgery in older individuals is a major clinical problem of uncertain mechanism; a similar cognitive decline also follows severe infection, chemotherapy, or trauma and is currently without effective therapy. A variety of mechanisms have been proposed, and exploring the role of inflammation, we recently reported the role of IL-1β in the hippocampus after surgery in mice with postoperative cognitive dysfunction. Here, we show that TNF-α is upstream of IL-1 and provokes its production in the brain. Peripheral blockade of TNF-α is able to limit the release of IL-1 and prevent neuroinflammation and cognitive decline in a mouse model of surgery-induced cognitive decline. TNF-α appears to synergize with MyD88, the IL-1/TLR superfamily common signaling pathway, to sustain postoperative cognitive decline. Taken together, our results suggest a unique therapeutic potential for preemptive treatment with anti-TNF antibody to prevent surgery-induced cognitive decline.